Interference minimization schemes in OFDMA-based femtocells - Habaebi, Mohamed Hadi; Chebil, Jalel; Zainal, Zulfadli; Muzaini, Afiq (INSI Publications, 2012)
Femtocells are deployed to improve the cellular coverage and network capacity in indoor area. Despite their great indoor coverage, the implementation of femtocell by high number of subscribers causes serious interference problem between femto Base Stations (fBSs) and cellular macro Base Stations (mBSs). In order to achieve interference avoidance in a two-tier femtocell network, self-organizing interference avoidance schemes are usually employed. In this paper, channel selection interference avoidance schemes are used to improve network performance. Simulation studies indicate that cumulative interference from macrocell and other femtocells reduces femtocell performances. However, by properly applying the channel selection schemes in conjunction with femtocell antenna beamforming technique, Signal to Interference and Noise Ratio (SINR) and the throughput of the femtocell are positively increased ensuring better network performance.